Operational optimization of reverse osmosis plant using MPC; Chemical Engineering Transactions; Vol. 45 - Manenti F. Flavio; Nadezhdin I. S. Igor Sergeevich; Goryunov A. G. Aleksey Germanovich; Kozin K. A. Kirill Andreevich; Baydali S. A. Sergey Anatolievich; Papasidero D . Davide; Rossi F. Francesco; Potemin R. V. Roman Valerjevich (2015, 2015)
Title screen